Pengembangan Media Pembelajaran VG-Plant Berbasis Articulate Storyline 3 pada Materi Perkembangbiakan Tumbuhan Kelas IV - Viena Aunillah Carl Vinson; I. Isrokatun; Ali Ismail (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study describes the process of developing VG-Plant learning media based on articulate storyline 3 on plant reproduction material in class IV elementary school. The purpose of this research is to determine the feasibility of VG-Plant media through the validation process of experts, measure the perception of media usability, and determine the compatibility of media on several different android version devices. The research was conducted using the Research and Development (R&D) method and the ADDIE model which goes through five stages, namely the analysis, design, development, implementation, and evaluation stages. The subject of this research was 32 fourth grade students and the feasibility of material and media was taken from the validation of experts. The results of this study are VG-Plant learning media relevant to the needs of the science learning process in grade IV on plant reproduction material. VG-Plant media design is made in the form of a.apk file. VG-Plant media is calculated using the Content Validity Index (CVI) and has the feasibility of content and media quality with a scale of 1 and in the